The effect of combined transcranial pulsed current stimulation and transcutaneous electrical nerve stimulation on lower limb spasticity in children with spastic cerebral palsy: a randomized and controlled clinical study - Zhenhuan Liu; Shangsheng Dong; Sandra Zhong; Fang Huang; Chuntao Zhang; Yuan Zhou; Haorong Deng (BMC, 2021)
Abstract Background In the current study, we applied a combination of non-invasive neuromodulation modalities concurrently with multiple stimulating electrodes. Specifically, we used transcranial pulsed current stimulation (tPCS) and transcutaneous electrical nerve stimulation (TENS) as a novel strategy for improving lower limb spasticity in children with spastic cerebral palsy (SCP) categorized on levels III-V of the Gross Motor Function Classification System (GMFCS) with minimal side effects. Methods Sixty-three SCP children aged 2-12 years, who were classified on levels III-V of the GMFCS were randomly assigned to one of two groups, resulting in 32 children in the experimental group and 31 children in the control group. The experimental group underwent a combination therapy of tPCS (400 Hz, 1 mA cerebello-cerebral stimulation) and TENS (400 Hz, max 10 mA) for 30 min, followed by 30 min of physiotherapy five times per week for 12 weeks. The control group underwent physiotherapy only 30 mins per day five times per week for 12 weeks. In total, all groups underwent 60 treatment sessions. The primary outcome measures were the Modified Ashworth Scale (MAS) and Modified Tardieu Scale (MTS). Evaluations were performed 3 days before and after treatment. Results We found a significant improvement in MAS and MTS scores of the lower limbs in the experimental group compared to the control group in the hip adductors (Left: p = 0.002; Right: p = 0.002), hamstrings (Left: p = 0.001; Right: p < 0.001, and gastrocnemius (Left: p = 0.001; Right: p = 0.000). Moreover, MTS scores of R1, R2 and R2-R1 in left and right hip adduction, knee joint, and ankle joint all showed significant improvements (p ≤ 0.05). Analysis of MAS and MTS scores compared to baseline scores showed significant improvements in the experimental group but declines in the control group. Conclusion These results are among the first to demonstrate that a combination of tPCS and TENS can significantly improve lower limb spasticity in SCP children classified on GMFCS levels III-V with minimal side effects, presenting a novel strategy for addressing spasticity challenges in children with severe SCP. Trial registration ChiCTR.org, ChiCTR1800020283, Registration: 22 December 2018 (URL: http://www.chictr.org.cn/showproj.aspx?proj=33953 ).